2021
DOI: 10.1161/jaha.120.018978
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity Burden and Adverse Outcomes After Transcatheter Aortic Valve Replacement

Abstract: Background Transcatheter aortic valve replacement (TAVR) has become the preferred treatment for symptomatic patients with aortic stenosis and elevated procedural risk. Many deaths following TAVR are because of noncardiac causes and comorbid disease burden may be a major determinant of postprocedure outcomes. The prevalence of comorbid conditions and associations with outcomes after TAVR has not been studied. Methods and Results This was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…2020 50 C 4 E 5731 74 ± 10.1 38.1 Feldman et al. 2021 51 C 3 L 341 81.4 ± 8 51.9 6.7 ± 4.8 86.8 Gracia et al. 2020 52 C 3 E 298 Testa et al.…”
Section: Resultsunclassified
“…2020 50 C 4 E 5731 74 ± 10.1 38.1 Feldman et al. 2021 51 C 3 L 341 81.4 ± 8 51.9 6.7 ± 4.8 86.8 Gracia et al. 2020 52 C 3 E 298 Testa et al.…”
Section: Resultsunclassified
“…Moreover, these patients may have a higher burden of comorbidity, an independent risk factor for post‐TAVR readmission and mortality. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…Given the increasing number of patients with these complex disease states, there is also an urgent need to better understand how complex co-morbidities influence the mechanism of AS initiation and progression of CAVD pathogenesis. Hypertension, type 2 diabetes mellitus, dyslipidemia, chronic kidney disease, chronic inflammatory diseases, and anemia are co-morbidities highly prevalent in AS patients (7)(8)(9)(10). The study by Roos et al identified a role for mitochondrial-derived oxidative stress in CAVD progression, suggesting a potential link between calcification processes related to metabolic shifts seen in obese or diabetic patients.…”
Section: Discussionmentioning
confidence: 99%